THE EFFECT OF MACHIAVELLIANISM ON ETHICAL PERCEPTION OF TAX EVASION WITH GENDER AS MODERATING VARIABLE - Ellyzabeth Putri Vizandra; Erina Sudaryati (AKUNTABILITAS, 2022)
ABSTRACTThis research is an empirical study that aims to determine the effect of machiavellianism on ethical perceptions of tax evasion with gender as a moderating variable. This research is a quantitative study with associative approach. Data collection methods used are by giving research questionnaires to respondents. The population of this research is the final student of S1 Accounting at Universitas Airlangga. The sample of this study was 167 people using a purposive sampling method. The analysis technique used is Moderated Regression Analysis (MRA). Based on the analysis and testing of hypotheses, it could be concluded that (1) Machiavellianism has a positive effects on ethical perceptions of tax evasion and (2) Gender moderates the effect of machiavellianism on ethical perceptions of tax evasion.Keywords: Machiavellianism, Ethical Perception, Tax Evasion, Gender